Sosialisasi Permainan Gasing Untuk Meningkatkan Konsentrasi Pada Siswa SMP Muhammadiyah 6 Samarinda - Jeane Betty Kurnia Jusuf; Nanda Alfian Mahardhika (Wadah Inovasi Indonesia, 2022)
IuM socialization of top games for Samarinda Muhammadiyah 6 Middle School students has several objectives: (1) to increase the concentration of junior high school students; (2) giving socialization to junior high school students about traditional top games; (3) increasing the interest of junior high school students in top games, (4) efforts to preserve traditional East Kalimantan games. In the current era the game is very minimal played by teenagers. This is due to the existence of modern games or online games that are more fun to be played by teenagers. Through this socialization, it is hoped that it can increase the interest of adolescents, especially students of towards top games. In addition, this service is expected to preserve local culture. The form of socialization of this service involved top players from the Kutai Kartanegara district to demonstrate how to play top. In the early stages of this service activity, the target of the IuM service team was all students. With the main goal of preserving East Kalimantan's local culture. Based on the results of the implementation of service in the form of socialization of the top games to increase the concentration of students. The results obtained were an increase in students' understanding of the top game, and students knew how to benefit from the top game in increasing concentration. In addition, the practice of how to play the top game, students were very enthusiastic in playing the top game.